2018
DOI: 10.1590/0104-1428.04117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the application of cashew gum as an excipient to produce tablets

Abstract: Cashew gum is extracted from the exudate of the giant cashew tree (Anacardium occidentale L.). The objective of this work was to study the extraction and purification of cashew gum through experiments to characterize its structures and physicochemical and thermal properties, and to evaluate its use as a pharmaceutical excipient. The characterization of the materials was performed by infrared spectroscopy, thermogravimetric analysis and rheological studies of powder. Analysis of the material showed that it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The thermogravimetric analysis of purified cashew gum ( Fig. 2A) showed three decomposition peaks, the first one at 46.36°C for water loss, the second and third at 222.73°C and 288.01°C respectively, show that the process of decomposition of the polysaccharides of this gum occurs in two stages, as described in the literature [18,53].…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 70%
See 2 more Smart Citations
“…The thermogravimetric analysis of purified cashew gum ( Fig. 2A) showed three decomposition peaks, the first one at 46.36°C for water loss, the second and third at 222.73°C and 288.01°C respectively, show that the process of decomposition of the polysaccharides of this gum occurs in two stages, as described in the literature [18,53].…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 70%
“…The spectra of the PCG (Fig. 1) and nystatin contained all the bands described in the literature and those of the mixtures showed that a rising concentration of PCG in the mixtures promoted broader bands, causing overlapping of the bands of the nys structure, as well as disappearance of the band of nystatin at 1004 cm -1 due to the widening of the band of PGC at 1070 cm -1 [18,43]. More importantly, there was no shift of the bands in the spectra, demonstrating the absence of physico-chemical interaction of the PCG, nystatin, flavoring agents and lubricating agent.…”
Section: Fourier-transform Infrared Spectroscopy (Ftir)mentioning
confidence: 59%
See 1 more Smart Citation
“…However, in the cited patent, the flocculant is obtained from cashew tree gum. Such gum is mainly composed of polysaccharides and it is produced by the stem in a process named gummosis, partially as a natural phenomenon, partially in response to heat, drought stress, mechanical injuries, and fungal or bacterial attack (Cunha et al, 2007;Pinto et al, 2018). On the other hand, condensed tannins from cashew trees are polyphenolic products that are a constituent part of the bark.…”
Section: Ftir Analysesmentioning
confidence: 99%
“…Cashew gum has been studied as an excipient for production of tablets with many functions, such as binding agent, drug release agent, mucoadhesive matrix for oral release, film forming agent for coating, and diluent agent [6,9,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%